LGU Access to Official Development Assistance (ODA): Status, Issues, and Concerns - Gilberto M. Llanto; Alex Jr. Brillantes; Ruperto P. Alonzo (Philippine Institute for Development Studies (PIDS), 2010)
Statistics on the distribution of ODA loans show that the local government sector is the smallest direct recipient of this funding source. While it has been observed that the amount of ODA grants and the number of ODA grant projects have been declining over the years, several factors could explain why LGUs have not been able to have a substantial share in ODA funds. The study discusses barriers to the greater of LGUs to ODA funds and provides specific recommendations for action by policymakers.
Keywords: 330; official development assistance; Philippines; ODA programming; grant financing framework; cost sharing; foreign borrowing act; Philippine Development Forum; Local Government Units (LGUs); Entwicklungshilfe; Kommunalverwaltung; Entwicklungsprojekt; Entwicklungspolitik; Philippinen